Minimally invasive procedures for urological disorders in pregnant patients: our experience - Dar, Manzoor Ahmad; Iqbal, Muzzain; Khawaja, Abdul Rouf; Wani, Mohammad Saleem; Bhat, Arif Hamid; Malik, Sajad Ahmad; Dar, Yaser Ahmad (International Surgery Journal, 2019)
Background: Urological disorders like stone disease, pyonephrosis secondary to obstruction and trauma are common during pregnancy with global incidence of 1 in 250 to 1 in 3000. These diseases can complicate any pregnancy and timely diagnosis and management is of utmost importance for safety of the mother and fetus. Managing these cases entails morbidity and minimally invasive procedures avoiding anesthesia have definite advantage. Methods: It was an observational study. Pregnant patients with nephrolithiasis, pyonephrosis, complicated post-traumatic ureteropelvic junction (PUJ) obstruction (PUJO) and trauma were included in the study. Results: Out of total 84 cases, 45 required intervention. Percutaneous nephrostomy (PCN) for pyonephrosis secondary to PUJO and obstructed PUJ calculus was done in 11 and 14 cases respectively. Bilateral PCN for bilateral nephrolithiasis was done in 7 cases. Silicon double-J stenting for ureteric calculus was done in 13 cases. One case of spontaneous fornicial rupture of kidney without stone disease was managed conservatively as were 4 cases of trauma with concomitant renal injury, 18 cases of non-obstructive renal stones and 16 cases of pyelonephritis. Seven patients lost follow-up. One case each of pyonephrosis and polytrauma had fetal death at term unrelated to urological cause. In rest 75 patients, primary pathology was tackled after 6-8 weeks of delivery. Conclusions: Urological diseases during pregnancy are not an uncommon entity and can pose risk to both mother and fetus. With good clinical vigil, use of minimally invasive procedures, close monitoring and follow up, these patients can be safely managed without any adverse events to the fetus and mother.